Skip to content
Related Articles
Get the best out of our app
GeeksforGeeks App
Open App

Related Articles

Power Rule in Derivatives

Improve Article
Save Article
Like Article
Improve Article
Save Article
Like Article

The power rule is a commonly used rule in derivatives. The power rule basically states that the derivative of a variable raised to a power n is n times the variable raised to power n-1. The mathematical formula of power rule can be written as: 

\dfrac{d}{dx}x^n=nx^{n-1} \\\qquad\\

Since differentiation is a linear operation on the space of differentiable functions, polynomials can also be differentiated using this rule. The power rule underlies the Taylor series as it relates a power series with a function’s derivatives.


Find the derivative of 

1. x101

\dfrac{d}{dx}x^n=nx^{n-1}\\\qquad\\ \implies \dfrac{d}{dx}x^{101}=101x^{100}\\\qquad\\

2. 15x6


Power Rule (with rewriting the expression)

From the above equation and example, you now know how to differentiate a variable raised to a power n. The point to be noted is that n can also be fractional and so the variable could have exponents and these exponents are real numbers. For better understanding check the following examples:

Find the derivative of

1.\ \ x^{\dfrac{-3}{4}}\\\qquad\\ \dfrac{d}{dx}x^{\dfrac{-3}{4}}\ =\ \dfrac{-3}{4}x^{\dfrac{-3}{4}-1}\ =\ \dfrac{-3}{4}x^{\dfrac{-3-4}{4}}\ =\ \dfrac{-3}{4}x^{\dfrac{-7}{4}} \\\qquad\\\qquad\\ 2. \ \ \sqrt{x}\\\qquad\\ \dfrac{d}{dx}\sqrt{x}\ =\ \dfrac{d}{dx}x^{\dfrac{1}{2}}=\dfrac{1}{2}x^{\dfrac{1}{2}-1}\ =\ \dfrac{1}{2}x^{\dfrac{-1}{2}}\ =\ \dfrac{1}{2\sqrt{x}} \\\qquad\\\qquad\\ 3. \ \ \dfrac{1}{\sqrt[3]{x}}\\\qquad\\ \dfrac{d}{dx}\dfrac{1}{\sqrt[3]{x}}\ =\ \dfrac{d}{dx}x^{\dfrac{-1}{3}}\ =\ \dfrac{-1}{3}x^{\dfrac{-1}{3}-1}\ =\ \dfrac{-1}{3}x^{\dfrac{-1-3}{3}}\ =\ \dfrac{-1}{3}x^{\dfrac{-4}{3}}\ =\dfrac{-1}{3\sqrt[3]{x^{4}}} \\\qquad\\\qquad\\ 4. \ \ \sqrt[5]{x^7}\\\qquad\\ \dfrac{d}{dx}\sqrt[5]{x^7}\ =\ \dfrac{d}{dx}x^{\dfrac{7}{5}}\ =\ \dfrac{7}{5}x^{\dfrac{7-5}{5}}\ =\ \dfrac{7}{5}x^{\dfrac{2}{5}} \\\qquad\\\qquad\\

Justifying the Power Rule 


Using the definition of derivative we can write

\dfrac{d}{dx}x^n\ as\ \lim\limits_{x\rarr0}\dfrac{(x+\triangle x)^n-x^n}{\triangle x}\\\qquad\\

By using binomial theorem we expand (x + △x)n th term

(x+\triangle x)^n\ term\\\qquad\\ \lim\limits_{x\rarr0}\dfrac{(x+\triangle x)^n-x^n}{\triangle x}\\\qquad\\ =\ \lim\limits_{x\rarr0}\dfrac{(\dbinom{n}{0}x^n+\dbinom{n}{1}x^{n-1}\triangle x+\dbinom{n}{2}x^{n-2}\triangle x^2....+\dbinom{n}{n}\triangle x^n)-x^n}{\triangle x}\\\qquad\\ =\ \lim\limits_{x\rarr0}\dfrac{\dbinom{n}{1}x^{n-1}\triangle x+\dbinom{n}{2}x^{n-2}\triangle x^2....+\dbinom{n}{n}\triangle x^n}{\triangle x}\\\qquad\\ = \ \lim\limits_{x\rarr0}\dbinom{n}{0}x^n+\dbinom{n}{1}x^{n-1}+\dbinom{n}{2}x^{n-2}\triangle x....+\dbinom{n}{n}\triangle x^n-1)-x^n\\\qquad\\ = \ \binom{n}{1}x^{n-1}\ =\ nx^{n-1} \\\qquad\\

Only the first term remained as it does not contain a △ x term hence,

\dfrac{d}{dx}x^n\ =\ nx^{n-1}

My Personal Notes arrow_drop_up
Last Updated : 24 Nov, 2022
Like Article
Save Article
Similar Reads
Related Tutorials